Measurements of four-lepton production at the Z resonance in pp collisions at sqrt[s] = 7 and 8 TeV with ATLAS. - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (2014)
Measurements of four-lepton (4ℓ, ℓ=e,μ) production cross sections at the Z resonance in pp collisions at the LHC with the ATLAS detector are presented. For dilepton and four-lepton invariant mass regions m(ℓ+ℓ(-)) > 5 GeV and 80